Long-term results of Dana-Farber Cancer Institute ALL Consortium protocols for children with newly diagnosed acute lymphoblastic leukemia (1985–2000) - Silverman, Lewis B. (2009)
The Dana-Farber Cancer Institute (DFCI) ALL Consortium has been conducting multi-institutional clinical trials in childhood ALL since 1981. The treatment backbone has included 20–30 consecutive weeks of asparaginase during intensification and frequent vincristine/corticosteroid pulses during the continuation phase. Between 1985–2000, 1457 children aged 0–18 years were treated on four consecutive protocols: 85-01 (1985–7), 87-01 (1987–91), 91-01 (1991–5) and 95-01 (1996–2000). The 10-year event-free survival (EFS) ± standard error by protocol was 77.9 ± 2.8% (85-01), 74.2± 2.3 (87-01), 80.8 ± 2.1% (91-01) and 80.5 ± 1.8% (95-01). Approximately 82% of patients treated in the 1980s and 88% treated in the 1990s were long-term survivors. Both EFS and overall survival (OS) rates were significantly higher for patients treated in the 1990s compared with the 1980s (p=0.05 and 0.01, respectively). On the two protocols conducted in the 1990s, EFS was 79–85% for T-ALL patients and 75–78% for adolescents (age 10–18 years). Results of randomized studies revealed that dexrazoxane prevented acute cardiac injury without adversely impacting EFS or OS in high-risk patients and frequently-dosed intrathecal chemotherapy was an effective substitute for cranial radiation in standard-risk patients. Current studies continue to focus on improving efficacy while minimizing acute and late toxicities.